2019
DOI: 10.1186/s12898-019-0241-0
|View full text |Cite
|
Sign up to set email alerts
|

Light pollution affects space use and interaction of two small mammal species irrespective of personality

Abstract: Background Artificial light at night (ALAN) is one form of human-induced rapid environmental changes (HIREC) and is strongly interfering with natural dark–light cycles. Some personality types within a species might be better suited to cope with environmental change and therefore might be selected upon under ongoing urbanization. Results We used LED street lamps in a large outdoor enclosure to experimentally investigate the effects of ALAN on activity patterns, movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 47 publications
0
12
1
1
Order By: Relevance
“…In contrast to the laboratory, we could not find an influence of partial nighttime illumination on the distribution of animals within grassland enclosures. In a previous study, we had found that animals increased their activity in illuminated enclosures compared to dark enclosures (Hoffmann et al, 2019), however, offering partial illumination in this study, we could not find a preference or avoidance for the illuminated part. A possible explanation for this could be that animals were able to avoid dim nighttime illumination by using vegetation cover and burrows.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…In contrast to the laboratory, we could not find an influence of partial nighttime illumination on the distribution of animals within grassland enclosures. In a previous study, we had found that animals increased their activity in illuminated enclosures compared to dark enclosures (Hoffmann et al, 2019), however, offering partial illumination in this study, we could not find a preference or avoidance for the illuminated part. A possible explanation for this could be that animals were able to avoid dim nighttime illumination by using vegetation cover and burrows.…”
Section: Discussioncontrasting
confidence: 89%
“…Nevertheless, there are several mammal species such as shrews, voles and lemurs that show a polyphasic activity pattern or cathemerality with activity bouts during both day and night (Curtis and Rasmussen, 2006;Halle, 2006) that might be strongly affected by ALAN as well. However, there are few studies, which focus on this group of species and/or chronotypes in the context of changing nighttime conditions (Hoffmann et al, 2018(Hoffmann et al, , 2019van Grunsven et al, 2018). These species might not only show changes in nocturnal behavior when subjected to ALAN but there might be carry-over effects to their diurnal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…A total of nine studies investigated behavioral and physiological responses in rodents when they were exposed to ALAN. Three studies on rodents demonstrated suppressed or decreased activity when they were exposed to ALAN [257][258][259]. In contrast, two studies reported increased activity in rodents when they were exposed to ALAN [260,261].…”
Section: Birdsmentioning
confidence: 99%
“…When foraging, pygmy mice are likely restricted to vegetation that shields them from the majority of light at night, whether it be the illumination of the moon or ALAN [60]. A previous study indicated that the presence of light at night affects the home range sizes of small rodents negatively and has implications for their movement patterns [78]. Current and future habitat transformation and degradation associated with urban expansion potentially pose a larger threat to the persistence of African pygmy mice in sub-urban and peri-urban areas.…”
Section: (C) Biological Implications For Pygmy Micementioning
confidence: 99%